Experimental study and prediction of abrasion resistance of hydraulic concrete - Qian Chen; Weizhun Jin; Xiaodan Tang; Hongxing Zhong; Qinghua Huang; Zhipeng Bai; Hongqiang Chu; Linhua Jiang (Case Studies in Construction Materials, 2025)
To predict the abrasion resistance of hydraulic concrete efficiently and accurately, this study analyzes the physical abrasion process of hydraulic concrete based on the underwater steel ball method. Additionally, building upon the principle of energy conservation, an energy equation relating fracture energy and abrasion strength of hydraulic concrete is established. The predictive fidelity of the energy equation is verified by analyzing the experimental results with different water-binder ratios (0.35, 0.4, and 0.45) and various fly ash contents (0 %, 15 %, and 20 %). The results show that with the increase of water-binder ratio, the abrasion strength of concrete first increases and then decreases. Adding 15 % fly ash can significantly improve the abrasion resistance of concrete, but the abrasion resistance will drop sharply when the dosage increases to 20 %. The fracture energy and abrasion strength of hydraulic concrete satisfy the energy equation regardless of the change of water-binder ratio or fly ash content. Subsequently, a wider range of different concrete mixtures can be used to evaluate the relationship between abrasion strength and fracture energy more scientifically and accurately, which provides theoretical guidance for predicting the abrasion strength of concrete in practical projects.